Assessment of Optical Quality at Different Contrast Levels in Pseudophakic Eyes - Chang Won Park; Hyojin Kim; Choun-Ki Joo (Journal of Ophthalmology)
Purpose. To assess visual function using Optical Quality Analysis System (OQAS) at varying levels of contrast in pseudophakic eyes. Methods. The study included patients admitted to Seoul St. Mary’s Hospital between January and February 2012: 143 pseudophakic eyes with one of five intraocular lens types, examined 2–6 months after cataract surgery, and 93 normal eyes (enhanced visual acuity (VA) < 0.1 logMAR) in age-matched controls. Subjects were examined at three contrast levels using the OQAS. Results. At 100%, 20%, and 9% contrast, simulated mean VA was 0.16±0.18 logMAR, 0.30±0.18 logMAR, and 0.52±0.17 logMAR, in normal eyes, and 0.16±0.12 logMAR, 0.33±0.20 logMAR, and 0.56±0.21 logMAR, respectively, in pseudophakic eyes. Simulated VA decreased significantly when contrast was reduced, regardless of ocular status, age group, and lens type (p<0.05). There were no significant differences between normal and pseudophakic eyes among subjects aged 50–69 (p>0.05). Among subjects aged 70–79, pseudophakic eyes showed improved simulated VA (p=0.000) and objective scattering index values (p=0.008). Conclusions. Patients with intraocular lenses have similar or superior visual function when compared to those with normal eyes at 2–6 months after cataract surgery, even under low-contrast conditions.